Correlating in vitro degradation and drug release kinetics of biopolymer-based drug delivery systems. Issue 1 (2nd January 2019) - Harting, R.; Johnston, K.; Petersen, S.
ABSTRACT: Polymers are becoming more important in all economic sectors, and as environmental concerns grow, biopolymers are replacing metal- or oil-based polymers. Two of these polymers are polyhydroxybutyrate (PHB), which is known for good mechanical characteristics and the manufacturing from renewable resources, and polylactic acid (PLA), which is known for fast degradation rates and great benefits for packaging industry. They exhibit properties that make them competitive alternatives for the less eco-friendly polymers, but processing techniques are not as well-researched. In this study, we performed in vitro degradation and drug release studies with pure PHB and PLA and PHB/PLA blends (1:3). Therefore, polymers were stored at 65°C in a PBS-buffer under rather static conditions to simulate intraossal localization. The mass loss of all samples indicates a degradation of all polymers, and it was confirmed by decreasing molecular weight, decreasing pH, increasing crystallinity, and decreasing water contact angle. Following these measurements, a 60-day drug release study was performed, which revealed a four-phase drug release mechanism, including a diffusion-controlled initial burst release especially elevated for investigated blends due to eased medium interpenetration, and a secondary burst release after 20 days for both blends and the pure PLLA-Biomer with lower molecular weight. The intensity of the secondary burst release corresponded to observed degradation characteristics allowing the conclusion of a degradation controlled drug release here.